Tepotinib treatment in patients with MET exon 14-skipping non-small cell lung cancer: long-term follow-up of the VISION phase 2 nonrandomized clinical trial - Mazieres, Julien; Paik, Paul K.; Garassino, Marina C.; Le, Xiuning; Sakai, Hiroshi; Veillon, Remi; Smit, Egbert F.; Cortot, Alexis B.; Raskin, Jo; Viteri, Santiago; Wu, Yi-Long; Yang, James C. H.; et al. (JAMA oncology, 2023)
MET inhibitors have recently demonstrated clinical activity in patients with MET exon 14 (METex14)-skipping non-small cell lung cancer (NSCLC); however, data with longer follow-up and in larger populations are needed to further optimize therapeutic approaches.To assess the long-term efficacy and safety of tepotinib, a potent and highly selective MET inhibitor, in patients with METex14-skipping NSCLC in the VISION study.The VISION phase 2 nonrandomized clinical trial was a multicohort, open-label, multicenter study that enrolled patients with METex14-skipping advanced/metastatic NSCLC (cohorts A and C) from September 2016 to May 2021. Cohort C (>18 months’ follow-up) was an independent cohort, designed to confirm findings from cohort A (>35 months’ follow-up). Data cutoff was November 20, 2022.Patients received tepotinib, 500 mg (450 mg active moiety), once daily.The primary end point was objective response by independent review committee (RECIST v1.1). Secondary end points included duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety.Cohorts A and C included 313 patients (50.8% female, 33.9% Asian; median [range] age, 72 [41-94] years). The objective response rate (ORR) was 51.4% (95% CI, 45.8%-57.1%) with a median (m)DOR of 18.0 (95% CI, 12.4-46.4) months. In cohort C (n = 161), an ORR of 55.9% (95% CI, 47.9%-63.7%) with an mDOR of 20.8 (95% CI, 12.6-not estimable [NE]) months was reported across treatment lines, comparable to cohort A (n = 152). In treatment-naive patients (cohorts A and C; n = 164), ORR was 57.3% (95% CI, 49.4%-65.0%) and mDOR was 46.4 (95% CI, 13.8-NE) months. In previously treated patients (n = 149), ORR was 45.0% (95% CI, 36.8%-53.3%) and mDOR was 12.6 (95% CI, 9.5-18.5) months. Peripheral edema, the most common treatment-related adverse event, occurred in 210 patients (67.1%) (35 [11.2%] experienced grade ≥3 events).The findings from cohort C in this nonrandomized clinical trial supported the results from original cohort A. Overall, the long-term outcomes of VISION demonstrated robust and durable clinical activity following treatment with tepotinib, particularly in the treatment-naive setting, in the largest known clinical trial of patients with METex14-skipping NSCLC, supporting the global approvals of tepotinib and enabling clinicians to implement this therapeutic approach for such patients.ClinicalTrials.gov Identifier: NCT02864992